AN EFFICIENT SIMULATED ANNEALING FOR A HYBRID FLOW SHOP SCHEDULING PROBLEM WITH SEQUENCE-DEPENDENT SETUP TIMES AND TWO OBJECTIVES - Mousavi, Seyyed Mostafa (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
The paper studies the problem of production scheduling of a set of independent jobs in the g-stage hybrid flow shop. To maximize external and internal efficiency, performance optimization of two functions, including maximum completion time and total tardiness, is intended simultaneously. Due to the dependency of scheduling activities on the times required to prepare the production processes, setup times are considered in the scheduling configurations. The bi-objective simulated annealing is proposed to handle the problem that belongs to the NP-hard class. The proposed algorithm is compared with another efficient algorithm in the literature (namely MOSA). The performance criterion based on the concept of data envelopment analysis, the Free Disposal Hull approach (FDH), is used to estimate the algorithm’s efficiency with respect to a set of efficient solutions. The results confirm that the set of efficient solutions of the proposed algorithm is more efficient than another algorithm.